The effect of soft skills in achieving superior performance of human resources: an analytical research in the faculties of the Iraqia University - Teacher Moaath Ghassan Ismail; Sumaya Abbas Majeed. Professor Dr (مجلة الدراسات الاقتصادية والادارية, 2024)
The research aimed to know the impact of soft skills as an independent variable and achieve superior performance in human resources as a responsive variable in the faculties of the Iraqi University, as well as to identify the levels of their availability and employment so that they are appropriate to the reality of the current conditions in the Iraqi academic environment. A set of hypotheses were formulated, the most important of which was the existence of a correlation. And the impact of soft skills and their dimensions in achieving superior performance for human resources, using the descriptive analytical research approach to explain the relationship and links between the research variables. Data was collected from respondents using a comprehensive inventory method, numbering (204) individuals, represented by a purposive sample of teachers who hold administrative positions (the dean and his assistants). And the scientific departments, divisions, and other administrative units), represented by (the College of Administration and Economics, the College of Mass Communication, the College of Law and Political Science, the College of Education/Tarmiya, the College of Education for Girls, the College of General Medicine, the College of Dentistry, the College of Arts, the College of Engineering, and the College of Islamic Sciences) This was based on a questionnaire that included (40) items, which were analyzed based on statistical programs (SPSS V 28.0) and Amos V 26.0. The most prominent result was the presence of a strong and positive effect of the soft skills variable on the superior performance of human resources, with the interest of university administrations in developing skills. It has human resources. And its increasing needs to increase communication and communication skills, work in a team spirit, and interest in critical and constructive thinking and time management in a way that is compatible with the nature of the university’s work.